Active Compounds of Sembung Leaves (Blumea balsamifera DC) in Silico Screening as Antihypertensives - Ahmad Sjahriza; Fyrda Shellia; Dyah Iswantini (JURNAL KIMIA MULAWARMAN, 2023)
Hypertension is a structural or functional change in the arteries or the organs it supplies caused by increased blood pressure. Angiotensin-converting enzyme (ACE) can increase blood pressure by converting inactive angiotensin I to active (angiotensin II). Captopril is a hypertension drug that can inhibit ACE activity. Sembung leaf (Blumea balsamifera DC) is a plant that can potentially have antihypertensive activity. This study aims to identify the interaction of active compounds in sembung leaves against ACE as antihypertensive drug candidates through an in silico test based on pharmacodynamic and pharmacokinetic parameters using two docking software, Autodock Vina and PyRx. The results showed that Luteolin was the best test ligand besides having lower ΔG and Ki than control ligands and higher Kd than control ligands. Luteolin was identified to interact with Zn and hydrogen bond interactions at the active site and met the criteria in Lipinski analysis, ADME, and toxicity, so this compound is relatively safe to be used as a drug candidate for the treatment of hypertension.